Indigenous methods for assessment of important aspects in undergraduates on pharmacology and therapeutics: a preliminary study - Balani, Naresh D.; Mahadkar, Namrata U.; Sonawane, Ritesh C. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: In pharmacology and therapeutics tutorial in current times is being disliked by most undergraduates. On the other hand, the important exercises related to analytical skill development, problem based exercise, rational use of medicine and individualized drug therapy need to be emphasize more in UG teaching and learning techniques. Methods: In the form of active learning we have framed CME pattern of conducting some important exercises including four above mentioned to facilitate the ability to think, feel or do the task which may be acceptable to the students better than or equivalent to tutorials. Results: We observed that 2 out of 8 willing participants scored higher than others in CME activity as well as terminal exams the other 2 scored borderline higher in CME activity than their score in terminal exams. Another 4 scored better in the terminal examinations as compared to CME activity.4 out of 8 i.e. 50% participants have shown acceptability as well as better performance in these exercises. Conclusions: All of these exercises are not in the curriculum/syllabus and there is no incentive of internal assessment on these. If these exercises are made mandatory, as it is the need of the hour, these can benefit the learner possibly by the way of change in their cognitive structure, keeping tutorials intact or removing them from syllabus.